Calculate the inverse Laplace transform of the function :
F(s) = (s+1)/ (s³+s²-6s)
"F(s)=\\frac{s+1}{s^3+s^2-6s}\\\\\n\\therefore F(s)\\\\\n=\\frac{s+1}{s^3+s^2-6s}\\\\\n=\\frac{(s+1)}{s(s-2)(s+3)}\\\\\n=\\frac{3}{10}\\times \\frac{1}{s-2}-\\frac{1}{6}\\times \\frac{1}{s}-\\frac{2}{15}\\times \\frac{1}{s+3}"
"So,"
"\\mathcal{L}^{-1}\\{F(s)\\}\n\\\\=\\mathcal{L}^{-1}\\{\\frac{3}{10}\\times \\frac{1}{s-2}-\\frac{1}{6}\\times \\frac{1}{s}-\\frac{2}{15}\\times \\frac{1}{s+3}\\}\n\\\\=\\frac{3}{10}\\mathcal{L}^{-1}\\left( \\frac{1}{s-2}\\right)-\\frac{1}{6}\\mathcal{L}^{-1}\\left( \\frac{1}{s}\\right)-\\frac{2}{15}\\mathcal{L}^{-1}\\left( \\frac{1}{s+3}\\right)\\\\\n=\\frac{3}{10}e^{2t}-\\frac{1}{6}\\times1-\\frac{2}{15}e^{-3t}\\\\\n=\\frac{3}{10}e^{2t}-\\frac{2}{15}e^{-3t}-\\frac{1}{6}"
"\\pmb\\therefore" Inverse laplace of of "\\pmb{F(s) :=\\frac{3}{10}e^{2t}-\\frac{2}{15}e^{-3t}-\\frac{1}{6}}"
Comments
Leave a comment